MASLAHAH DAN BATASAN-BATASANNYA MENURUT AL-BÛTHÎ (Analisis Kitab Dlawâbith al-Mashlahah fi al-Syarî’ah al-Islâmiyyah) - Arfan, Abbas (Fakultas Syariah, 2013)
Definition of al - mashlahah according to al - BÃ»thÃ® is : â€œ Something useful accoding to al - ShÃ¢ri â€˜ (Allah and His Messenger ) for the benefit of his servants , in keeping religion , life , intellect , lineage and their property , in accordance with the specific sequences contained in the maintenance category . â€œ Furthermore al - BÃ»thÃ® asserts that al - mashlahah can be used as a source of law if it meets the five criteria that he called al -mashlahah DlawÃ¢bith.Â TheseÂ fiveÂ criteria Â areÂ ;Â (Â a)Â maslahahÂ shouldÂ be included in the scope of al - maqashid al - Syarâ€™iyyah the five , ( b ) maslahah does not contradict with the Qurâ€™an , ( c ) maslahah does not contradict with al - Sunnah , ( d ) maslahah does not contradict with al - Qiyas and ( e ) maslahah does not contradict with another benefit that is higher / stronger / more important . Thatâ€™s more or less the gist of the book DlawÃ¢bith mashlahah fi al - Shariâ€™ah al - Islamiyya , beside that in this paper , the authors tried to analyze critic al - BÃ»thÃ® against al - ThÃ»fÃ® on maslahah concept , in addition also critical analysis of the author to distribution and limitations of maslahah in al - BÃ»thÃ®â€™s version. DefinisiÂ al-MashlahahÂ menurutÂ al-BÃ»thÃ®Â adalah:Â â€œSesuatuÂ yangÂ bermanfaat yang dimaksudkanÂ olehÂ al-Syariâ€™Â (AllahÂ danÂ Rasul-Nya)Â untukÂ kepentingan hamba-Nya,Â baikÂ dalamÂ menjagaÂ agama,Â jiwa,Â akal,Â keturunanÂ danÂ harta mereka,Â sesuaiÂ denganÂ urutanÂ tertentuÂ yangÂ terdapatÂ diÂ dalamÂ kategori pemeliharaan tersebut.â€ Namun al-BÃ»thÃ® menegaskan bahwa al-Mashlahah dapat dijadikan sebagai sumber hukum jika memenuhi lima kriteria yang ia istilahkan dengan DlawÃ¢bithÂ al-Mashlahah.Â KelimaÂ kriteriaÂ tersebutÂ adalah;Â Â maslahah tersebut haruslah: (a) termasuk ke dalam cakupan al-MaqÃ¢shid al-Syarâ€™iyyah yang lima, (b) tidak bertentangan dengan al-Qurâ€™an, (c) tidak bertentangan dengan alSunnah, (d) tidak bertentangan dengan al-Qiyas dan (e) tidak bertentangan dengan kemaslahatanÂ lainÂ yangÂ lebihÂ tinggi/Â lebihÂ kuat/lebihÂ penting.Â Itulah lebih kurang intisariÂ dariÂ kitabÂ Â DlawÃ¢bithÂ al-Mashlahah fiÂ SyarÃ®â€™ahÂ al-IslÃ¢miyyah,Â namun dalam makalah ini, penulis berusaha menganalisis kritik al-BÃ»thÃ® terhadap konsep maslahah al-ThÃ»fÃ®, disamping analisis kritis penulis terhadap pembagian maslahah dan batasannya versi al-BÃ»thÃ®.